2004
DOI: 10.1186/1471-2156-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Ordered subset linkage analysis supports a susceptibility locus for age-related macular degeneration on chromosome 16p12

Abstract: Background: Age-related macular degeneration (AMD) is a complex disorder that is responsible for the majority of central vision loss in older adults living in developed countries. Phenotypic and genetic heterogeneity complicate the analysis of genome-wide scans for AMD susceptibility loci. The ordered subset analysis (OSA) method is an approach for reducing heterogeneity, increasing statistical power for detecting linkage, and helping to define the most informative data set for follow-up analysis. OSA assesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…A concordance for AMD phenotypes in twins, and a higher risk of siblings of individuals with AMD have been reported [13], [14], [15], [16], [17], [18]. These early studies lead to genome-wide linkage analyses using microsatellite markers to search for chromosomal regions associated with affected individuals [19], [20], [21], [22], [23], [24], [25], [26], [27]. Several candidate regions including 1q32 and 10q26 were confirmed by a metaanalysis [28].…”
Section: Introductionmentioning
confidence: 95%
“…A concordance for AMD phenotypes in twins, and a higher risk of siblings of individuals with AMD have been reported [13], [14], [15], [16], [17], [18]. These early studies lead to genome-wide linkage analyses using microsatellite markers to search for chromosomal regions associated with affected individuals [19], [20], [21], [22], [23], [24], [25], [26], [27]. Several candidate regions including 1q32 and 10q26 were confirmed by a metaanalysis [28].…”
Section: Introductionmentioning
confidence: 95%
“…For example, sibling pairs concordant for advanced AMD from the Family Age-related Maculopathy Study (FARMS) showed significant linkage to 5q33.3, 14q32.33, 16p13.13, 19q13.31, 21q21.2, 40 while other investigators who also studied populations characterized by advanced AMD did not report significant linkage to these same regions. 34,37,104,105 Similarly, an association between advanced AMD and the 16p12 region has been observed to be dependent on factors such as body mass index (BMI) and hypertension in some studies 38 , but not others. 37 In summary, genome wide scans employing both linkage and genome wide association methods have helped to identify candidate genes for AMD and candidate regions in need of further investigation.…”
Section: Genome Wide Scansmentioning
confidence: 99%
“…Unlike ABCA4, ELOVL4 is located in a region (6q24–q14) previously identified from genome-wide scans to harbor AMD susceptibility genes. 35,38 A five base pair deletion in this gene has been found to be associated with an autosomal dominant Stargardt-like macular dystrophy, which has phenotypic similarity to the dry or atrophic form of AMD. The M299V (rs3812153) variant of ELOVL4 has been demonstrated to increase risk of neovascular AMD, 90 although an earlier study did not find this association for either the early or more advanced stages of AMD.…”
Section: Genes Associated With Juvenile (Mendelian) Forms Of Macular mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common approach to heterogeneity is to try to remove its confounding effect by data stratification. This has been done using strategies such as ordered subset analysis,23 latent class analysis,24 25 tree-based recursive partitioning,26 and clustering 2728 These methods preprocess the dataset based on genetic risk factors, demographic data, phenotypic data, or endophenotypes in order to form more homogeneous subsets of subjects.…”
Section: Background and Significancementioning
confidence: 99%